Application of Spontaneous Photon Emission in the Growth Ages and Varieties Screening of Fresh Chinese Herbal Medicines. (31st January 2017) - Zhao, Xiaolei; Pang, Jingxiang; Fu, Jialei; Yang, Meina; Van Wijk, Eduard; Liu, Yanli; Fan, Hua; Zhang, Yufeng; Han, Jinxiang
Abstract : Ultraweak photon emission emitted by all living organisms has been confirmed to be a noninvasive indicator for their physiological and pathological characteristics. In this study, we investigated the characteristics of spontaneous photon emission (SPE) and the contents of specific active compounds of roots and flowers buds of several fresh Chinese herbal medicines (natural medicines) with different growth ages and varieties. The results revealed that the contents of specific active compounds from same species herbs with different growth ages and varieties were significantly different, and this difference could be reflected by their SPE. Because the contents of specific bioactive constituents in Chinese herbs are closely related to their quality and curative effect, the SPE measurement technique may contribute to the quality control of Chinese herbal medicine in the future.